2017
DOI: 10.1002/jcp.26024
|View full text |Cite
|
Sign up to set email alerts
|

TNF‐α has both stimulatory and inhibitory effects on mouse monocyte‐derived osteoclastogenesis

Abstract: Phenotypically different osteoclasts may be generated from different subsets of precursors. To what extent the formation of these osteoclasts is influenced or mediated by the inflammatory cytokine TNF‐α, is unknown and was investigated in this study. The osteoclast precursors early blasts (CD31hiLy‐6C−), myeloid blasts (CD31+Ly‐6C+), and monocytes (CD31−Ly‐6Chi) were sorted from mouse bone marrow using flow cytometry and cultured with M‐CSF and RANKL, with or without TNF‐α. Surprisingly, TNF‐α prevented the di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
28
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 37 publications
1
28
0
Order By: Relevance
“…Although the above two genetic models showed that the upper bound of 95% CI exceeded 1 (1.053) or closed to 1 (0.999), the presence of the -238 A allele was considered a trend to decrease the risk of STB. The regulatory role of TNF- α in the differentiation of osteoclast might be related to this [ 34 ]. However, we failed to find any association of TNF-α -308G>A polymorphism with PTB and STB in our study populations.…”
Section: Discussionmentioning
confidence: 99%
“…Although the above two genetic models showed that the upper bound of 95% CI exceeded 1 (1.053) or closed to 1 (0.999), the presence of the -238 A allele was considered a trend to decrease the risk of STB. The regulatory role of TNF- α in the differentiation of osteoclast might be related to this [ 34 ]. However, we failed to find any association of TNF-α -308G>A polymorphism with PTB and STB in our study populations.…”
Section: Discussionmentioning
confidence: 99%
“…However, LPS is only a relevant stimulus in septic bone diseases, whereas most osteoclast-associated conditions, including a plethora of arthritis, involve sterile inflammatory conditions in which S100A8/A9 is strongly increased. Other factors that have been described to inhibit precursor-to-osteoclast differentiation are IL-1b and TNF-a (41,42). Together, these studies suggest that the timing of exposure to proinflammatory factors like S100A8/A9 in the course of osteoclast differentiation might act as a switch to determine the osteoclast fate.…”
Section: Discussionmentioning
confidence: 77%
“…Together, these data indicate that the S100A9 effects are directly affecting the RANK expression levels rather than indirectly via decreased expression of the M-CSF receptor. Interestingly, we showed that both IL-1b and TNF-a secretion were increased after exposure to S100A9, which has been shown to reduce osteoclast differentiation from precursors (41,42). However, after exposure to S100A9, addition of IL-1RA to block IL-1 did not rescue the membrane expression of RANK.…”
Section: Discussionmentioning
confidence: 79%
“…Together, this inflammatory scene within the soft connective tissue of the periodontium sets the stage for activation of osteoclast precursors, where inflammatory cytokines such as IL-1β [ 14 ] and TNF-α [ 15 ] will enhance osteoclast formation and activity. However, this view does not take into account the recent appraisal of the osteocyte as a major RANKL producing cell [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%